3,4-Methylenedioxy methamphetamine, synthetic cathinones and psychedelics: From recreational to novel psychotherapeutic drugs - López-Arnau, Raúl; Camarasa, Jordi; Carbó, Marcel·lí; Nadal-Gratacós, Núria; Puigseslloses, Pol; Espinosa-Velasco, María; Urquizu, Edurne; Escubedo, Elena; Pubill, David (Frontiers in Psychiatry, 2022)
The utility of classical drugs used to treat psychiatric disorders (e.g., antidepressants, anxiolytics) is often limited by issues of lack of efficacy, delayed onset of action or side effects. Psychoactive substances have a long history of being used as tools to alter consciousness and as a gateway to approach the unknown and the divinities. These substances were initially obtained from plants and animals and more recently by chemical synthesis, and its consumption evolved towards a more recreational use, leading to drug abuse-related disorders, trafficking, and subsequent banning by the authorities. However, these substances, by modulation of certain neurochemical pathways, have been proven to have a beneficial effect on some psychiatric disorders. This evidence obtained under medically controlled conditions and often associated with psychotherapy, makes these substances an alternative to conventional medicines, to which in many cases the patient does not respond properly.. Such disorders include post-traumatic stress disease and treatment-resistant depression, for which classical drugs such as MDMA, ketamine, psilocybin and LSD, among others, have already been clinically tested, reporting successful outcomes. The irruption of new psychoactive substances (NPS), especially during the last decade and despite their recreational and illicit uses, has enlarged the library of substances with potential utility on these disorders. In fact, many of them were synthetized with therapeutic purposes and were withdrawn for concrete reasons (e.g., adverse effects, improper pharmacological profile). In this review we focus on the basis, existing evidence and possible use of synthetic cathinones and psychedelics (specially tryptamines) for the treatment of mental illnesses and the properties that should be found in NPS to obtain new therapeutic compounds.